Fluazuron efficacy against Rhipicephalus microplus (Acari: Ixodidae) in cattle: Systemic exposure and pattern of tick drug uptake - Sarli, Macarena (2025)
The aims of this work were to evaluate the relevance of the tick attachment site on the host’s body in the fluazuron (FZN) uptake by ticks through direct contact, characterizing the early distribution of the drug through the skin and adipose tissue of different anatomical regions. Additionally, characterize how the systemic exposure (plasma availability) of FZN affects its efficacy against Rhipicephalus microplus. Five heifers were experimentally infested with R. microplus larvae and topically treated with FZN. Ticks exposed (TE) to direct topical contact with the drug—either in the dorsal (DTE) or ventral (VTE) areas of each heifer's body—or not exposed (TNE), were collected at 12 and 24 h post-treatment (PT). Skin and adipose tissue biopsies were taken at 12 h, 1 day and 10 days PT. Fluazuron concentrations in plasma, tissues and ticks were measured HPLC. Tick counts were performed from day 0 to day 38 PT. Mean FZN concentrations were similar in DTE and VTE and significantly higher than in TNE at 24 h PT. Dorsal and ventral skin samples showed comparable FZN levels. The area under the plasma concentration–time curves (AUC)₀₋₃₁ ranged from 589 to 1276 ng⋅d/mL. A negative correlation was observed between FZN plasma AUC3–17 and tick counts at day 17 PT. Results confirm that FZN is absorbed through the tick’s integument by direct contact independently of the attachment site. Fluazuron plasma concentrations of 20–25 ng/mL appear necessary to achieve optimal efficacy. Inter-animal variability in FZN exposure after topical application affects treatment efficacy against cattle ticks.